Anlotinib Downregulates RGC32 Which Provoked by Bevacizumab - Liu, Zhujun; Qin, Tingting; Yuan, Xiaohan; Yang, Jie; Shi, Wei; Zhang, Xiaoling; Jia, Yanan; Liu, Shaochuan; Wang, Jing; Li, Kai (Frontiers in Oncology, 2022)
Background: Bevacizumab is the representative drug in antiangiogenic therapy for lung cancer. However, it induced resistance in some neoplasm. Anlotinib, a novel multi-target tyrosine kinase inhibitor which has an inhibitory action on both angiogenesis and malignancy, is possible to reverse the resistance. Methods: Transwell migration and invasion experiments of bevacizumab with or without anlotinib were conducted to verify the activated/inhibited ability of lung adenocarcinoma cells. We sequenced A549 cells with enhanced migration and invasion abilities after bevacizumab treatment, screened out the differentially expressed gene and further confirmed by western blot and q-PCR assays. We also investigated immunohistochemical staining of tumor tissue in mice and human lung adenocarcinoma. Results: Bevacizumab facilitated migration and invasion of lung adenocarcinoma cells. Differentially expressed gene RGC32 was screened out. Bevacizumab upregulated the expression of RGC32, N-cadherin, and MMP2 through ERK-MAPK and PI3K-AKT pathways. Anlotinib downregulated their expression and reversed the effect of bevacizumab on A549 cells. In vivo experiments confirmed that higher-dose bevacizumab facilitated metastasis in tumor-bearing nude mice and upregulated the expression of RGC32, N-cadherin, and MMP2, whereas anlotinib abrogated its effect. Expression of both RGC32 and N-cadherin positively correlated with lymph node metastasis and stage in lung adenocarcinoma was found. Survival analysis revealed that higher expressions of RGC32 and N-cadherin were associated with poor progression-free survival and overall survival. Conclusions: Bevacizumab may promote invasion and metastasis of lung adenocarcinoma cells by upregulating RGC32 through ERK-MAPK and PI3K-AKT pathways to promote epithelial–mesenchymal transition, whereas anlotinib reverses the effect. RGC32 and N-cadherin are independent prognostic factors in lung adenocarcinoma.